Judicialização da saúde: escolhas trágicas necessárias a uma correta categorização dos direitos para a oferta de soluções abrangentes - Rezende, Kid Lenier (2024)
The judicialization of the right to health is a complex and growing phenomenon, in which citizens seek to guarantee access to treatments and medicines not available by the public health system through legal actions. Given this scenario, new mechanisms have emerged to assist and organize this judicialization process, such as the recognition of general repercussion by the Federal Supreme Court, which establishes a judgment necessary to establish a thesis to assist other judicial bodies in the analysis of complex demands. , mainly involving the right to health, involving procedures with new interinstitutional communication channels to produce a socially fair decision; the objectification of the processes initially proposed to satisfy subjective interests; the structuring of a system of precedents, stabilizing social expectations, with the binding of the Courts and first-degree judges. This dissertation investigates such mechanisms based on existing research, with a special focus on decisions of general repercussion handed down by the Federal Supreme Court (STF). The research examines the STF's performance in emblematic cases related to the right to health and how these decisions impact new judicialization mechanisms. The methodological approach includes a systematic review of the literature on health judicialization, analyzing studies that discuss the characteristics and effects of the new mechanisms created. The results reveal that the judicialization of the right to health has led to an overload of the judicial system and generated financial impacts for the State. Furthermore, an increase in the use of new mechanisms has been identified, such as the creation of technical chambers, admission of amicus curiae and the holding of public hearings, to facilitate the judicialization process. The analysis of decisions of general repercussion within the scope of the STF demonstrates a tendency towards recognition and protection of fundamental rights related to health, with the prevalence of the principle of human dignity and the right to life as foundations for decisions. However, there is also concern about the budgetary impact of legal demands on public health, which has led the STF to establish stricter criteria for granting high-cost medicines and treatments. Given these results, the dissertation proposes reflections on the balance between access to justice and the financial sustainability of the health system. It also suggests the need to improve dialogue mechanisms between the Executive, Legislative and Judiciary branches to seek more effective solutions to guarantee the right to health without overloading the judicial system. Furthermore, it highlights the importance of a holistic and multidisciplinary approach to tackling the problem, considering legal, political, economic and social aspects involved in the judicialization of the right to health.